Grupo de investigación emergencias y desastres (2001)
ABSTRACT: A presentation is made of the sociopolitical, juridical and environmental context in which disasters and emergencies happen, which supports the importance of carrying out studies that, from the psycho-social and the health attention points of view, contribute to prevention, attention, mitigation, and to the rehabilitation of individuals and communities. Also presented are research projects, extension and training activities, publications and reports, national and international contacts, participation in the formation of specialization and undergraduate level students, and bibliographical references. Disasters are one the main problems, producing different situations that alter the life quality of communities. For research work, problematic nuclei are considered to be: trauma, self-care, physical and psycho-social repercussions, community participation and forced displacement.